Ni-Catalyzed Reductive Coupling of Alkyl Carbonochloridates and Aryl Iodides - Liu, Chonghuo; Yao, Ken; Chen, Yunrong (Synlett, 2023)
A Ni-catalyzed reductive coupling of alkyl carbonochloridates and aryl iodides for the synthesis of aromatic esters has been developed. The present method is a new type of reductive coupling for building Csp2-CO bonds, and it avoids using toxic carbon monoxide gas. It tolerates various aryl iodides, and a coordinating group in alkyl carbonochloridates is key to improving the yield of the reaction.